Genetic improvement of the chemical composition of Scots pine (Pinus sylvestrisL.) juvenile wood for bioenergy production - Funda, Tomas; Fundova, Irena; Fries, Anders; Wu, Harry (2020)
Chemical composition is one of the key characteristics that determines wood quality and in turn its suitability for different end products and applications. The inclusion of chemical compositional traits in forest tree improvement requires high-throughput techniques capable of rapid, non-destructive and cost-efficient assessment of large-scale breeding experiments. We tested whether Fourier-transform infrared (FTIR) spectroscopy, coupled with partial least squares regression, could serve as an alternative to traditional wet chemistry protocols for the determination of the chemical composition of juvenile wood in Scots pine for tree improvement purposes. FTIR spectra were acquired for 1,245 trees selected in two Scots pine (Pinus sylvestrisL.) full-sib progeny tests located in northern Sweden. Predictive models were developed using 70 reference samples with known chemical composition (the proportion of lignin, carbohydrates [cellulose, hemicelluloses and their structural monosaccharides glucose, mannose, xylose, galactose, and arabinose] and extractives). Individual-tree narrow-sense heritabilities and additive genetic correlations were estimated for all chemical traits as well as for growth (height and stem diameter) and wood quality traits (density and stiffness). Genetic control of the chemical traits was mostly moderate. Of the major chemical components, highest heritabilities were observed for hemicelluloses (0.43-0.47), intermediate for lignin and extractives (0.30-0.39), and lowest for cellulose (0.20-0.25). Additive genetic correlations among chemical traits were, except for extractives, positive while those between chemical and wood quality traits were negative. In both groups (chemical and wood quality traits), correlations with extractives exhibited opposite signs. Correlations of chemical traits with growth traits were near zero. The best strategy for genetic improvement of Scots pine juvenile wood for bioenergy production is to decrease and stabilize the content of extractives among trees and then ...